Mathematical modelling for proton exchange membrane fuel cell (PEMFC) - Azri, M.; Mubin, A.N.A.; Ibrahim, Z.; Rahim, N.A.; Raihan, S.R.S. (Asian Research Publishing Network, 2016)
Proton Exchange Membrane Fuel Cell (PEMFC) is one type of the renewable energy that are current increasingly popular in industry. The cost for the implementation of the PEMFC system is quite high in order to use in the experimental research field. Therefore, the simulation modelling is very useful to emulate the PEMFC system in real work. The objective of this paper is to develop the simple mathematical equation for steady-state and thermodynamic modelling based on the equivalent electrical circuit of the PEMFC. The Matlab/Simulink is used to simulate the modelling based on the practical parameters of the Horizon H-500 fuel cell stack. Comparison performance of parameters affects on the PEMFC model is investigated. The graph for I-P curve, I-V curve and the losses involve in the reaction are discussed.